(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
One effective way to improve language learning and student engagement is to incorporate multidisciplinary ideas into foreign language instruction. Teachers can create a more comprehensive learning environment that promotes cognitive growth and cultural understanding by tying language education into disciplines like history, science, math, and the arts. The theoretical underpinnings of interdisciplinary teaching are examined in this work, along with different approaches to integrating interdisciplinary tactics in language classes and the advantages and difficulties of doing so. This study highlights the importance of multidisciplinary links in developing learners’ global and linguistic competency by showcasing successful case studies and best practices.